Alantolactone inhibits growth of K562/adriamycin cells by downregulating Bcr/Abl and P‐glycoprotein expression. Issue 5 (26th February 2013) - Yang, Chunhui; Yang, Jingbo; Sun, Meiyan; Yan, Jiangzhou; Meng, Xiuxiang; Ma, Tonghui
Abstract Alantolactone, a sesquiterpene lactone containing an α‐methylene‐γ‐lactone group, is the active component of Inula helenium (Compositae), a traditional Chinese medicinal herb. It has been reported that alantolactone has the capacity to inhibit tumor cell growth through induction of apoptosis. The purpose of this study was to assess the effects of alantolactone in the adriamycin (ADR)‐resistant human erythroleukemia cell line K562/ADR, and provide evidence that it might function as a potent therapeutic agent in chronic myelogenous leukemia (CML) patients with Bcr/Abl and the multidrug‐resistance phenotype. Our results showed that alantolactone significantly inhibited K562/ADR cell growth by downregulating Bcr/Abl and P‐glycoprotein expression. Alantolactone also induced apoptosis via modulation of protein levels of Bcl‐2 family members, caspase activation, poly ADP ribose polymerase cleavage, and cytochrome C release. We also observed that alantolactone induced cell‐cycle arrest in the G2/M phase, downregulated cyclin B1 and cyclin‐dependent protein kinase 1, and upregulated the cyclin‐dependent kinase inhibitor p21. Together, these results demonstrate that alantolactone may be a potent therapeutic agent against CML, and a potential Bcr/Abl inhibitor. © 2013 IUBMB Life., 65(5):435–444, 2013.